Negotiating the Social Organization of School Library Work: An Institutional Ethnography - Crispin, Jennifer (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This institutional ethnography starts from the standpoint of a school librarian to examine how school library work is coordinated and explained by social institutions. Areas of focus include the work of accounting for materials, the work of accounting for students, and the work of understanding and negotiating schedules. Cette ethnographie institutionnelle s'appuie sur le bibliothécaire en milieu scolaire et examine comment les institutions sociales coordonnent et justifient le travail au sein de la bibliothèque scolaire. Les points à l'étude comprennent : les efforts de justification du matériel, les efforts de représentation des étudiants et les efforts de compréhension et de négociation des horaires.